Dimeric binding of plant alkaloid ellipticine to human serum proteins. Issue 50 (4th May 2016) - Zsila, Ferenc; Beke-Somfai, Tamás
Abstract : Induced exciton circular dichroism signals reveal the accommodation of a pair of ellipticine molecules to the subdomain IB of human serum albumin and the β-barrel of α1 -acid glycoprotein. Abstract : Human serum albumin (HSA) binding of anticancer plant alkaloid ellipticine has been studied in conjunction with assessing its association to serum α1 -acid-glycoprotein (AAG). Taking advantage of the ability of chiral protein environments to induce optical activity, circular dichroism (CD) spectroscopy was employed to characterize the alkaloid-protein non-covalent adducts. CD competition experiments revealed the simultaneous accommodation of two ellipticine molecules within the large crevice of HSA located in subdomain IB that induces an exciton coupling signature in the CD spectrum. Note that subdomain IIA was also found to host an ellipticine molecule. Supporting molecular docking simulations were also performed, which showed a hydrophobicity-driven stabilization of two ellipticine molecules within subdomain IB in a left-handed helical orientation. Similar to HSA, a pair of alkaloid ligands are inserted into the β-barrel cavity of AAG producing a polyphasic CD curve. The 'F1/S' and 'A' genetic variants of the protein bind ellipticine with comparable affinity albeit the distinct topography of the pockets provokes large intensity differences in the CD signals.